Bitcoin return dynamics volatility and time series forecasting - Anand, Punit; Sharan, Anand Mohan (International Journal of Financial Studies, 2025)
Bitcoin and other cryptocurrency returns show higher volatility than equity, bond, and other asset classes. Increasingly, researchers rely on machine learning techniques to forecast returns, where different machine learning algorithms reduce the forecasting errors in a high-volatility regime. We show that conventional time series modeling using ARMA and ARMA GARCH run on a rolling basis produces better or comparable forecasting errors than those that machine learning techniques produce. The key to achieving a good forecast is to fit the correct AR and MA orders for each window. When we optimize the correct AR and MA orders for each window using ARMA, we achieve an MAE of 0.024 and an RMSE of 0.037. The RMSE is approximately 11.27% better, and the MAE is 10.7% better compared to those in the literature and is similar to or better than those of the machine learning techniques. The ARMA-GARCH model also has an MAE and an RMSE which are similar to those of ARMA.
Number: 2
Keywords: ARMA; ARMA-GARCH; Econometrics; Economics; Financial economics; MAE; Mathematics; RMSE; Series (stratigraphy); Statistics; Time series; Volatility (finance); bitcoin; dept.fin; time series

US bank lending to small businesses: an analysis of covid-19 and the paycheck protection program - Abugri, Benjamin A.; Osah, Theophilus T. (Journal of Risk and Financial Management, 2025)
This paper examines the characteristics of banks and their lending behavior in relation to Paycheck Protection Program (PPP) loans and commercial and industrial (C&I) loans to small businesses during the COVID-19 pandemic. Our findings show that lenders facing greater risk tended to lend more PPP loans, consistent with the risk-aversion theory. Specifically, banks with a higher loan–deposit ratio, lower overall profitability, poorer loan quality, and higher exposure to risks in business (C&I) loans are characterized by higher PPP loans. C&I loans to all businesses are negatively related to the loan–deposit ratio and loan loss allowance ratio, but are positively linked with the capital ratio. However, we find important differences in C&I lending to small businesses versus large businesses. Furthermore, there is evidence regarding the success of targeting PPP loans towards more productive sectors of the US economy. Using FDIC-defined banks’ lending specializations, we show that banks focused on international lending had a limited role in PPP lending.
Number: 5
Keywords: 2019-20 coronavirus outbreak; Business; COVID-19 pandemic; Coronavirus disease 2019 (COVID-19); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); US banks; Virology; commercial and industrial loans; dept.fin; paycheck protection program; peer-reviewed; risk aversion; small business lending